2017
DOI: 10.17586/2220-8054-2017-8-4-413-419
|View full text |Cite
|
Sign up to set email alerts
|

The loaded parabolic-hyperbolic equation and its relation to non-local problems

Abstract: In this present paper, unique solvability is proved for the boundary value problems for the loaded differential equations associated with non-local boundary value problems, for the classical partial differential equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…[4], Zikirov O. S. and Kholikov D. K. [5], Kh. Belakroum, A. Ashyralyev, A. Guezane-Lakoud [6], Khashimov A. R, Smetanová D. [7], as well as in [8,9].…”
Section: Introduction and Formulation Of The Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…[4], Zikirov O. S. and Kholikov D. K. [5], Kh. Belakroum, A. Ashyralyev, A. Guezane-Lakoud [6], Khashimov A. R, Smetanová D. [7], as well as in [8,9].…”
Section: Introduction and Formulation Of The Problemmentioning
confidence: 99%
“…We can cite by many examples as which emphasized the development of the theory of the loaded equation in the last several decades. As we know [1], mathematical models of nonlocal physics-biological fractal processes represented by loaded integro-differential equations or loaded differential equations especially with integro-differential operators [1,9].…”
Section: Introduction and Formulation Of The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Local and nonlocal problems for second-order partial dierential equations of hyperbolic and mixed types with loaded terms in special domains were considered in [18]- [22]. In the study of these problems, the problem of studying integral and integro-dierential equations arises.…”
Section: Introductionmentioning
confidence: 99%
“…The field of partial differential equations of fractional order is experiencing a sustained growing interest in the recent years, see for instance the previous studies. () From the available bibliography, it is observed that the boundary‐value problems for a third‐order loaded differential equations containing mixed parabolic‐hyperbolic and elliptic‐parabolic operators in the principal part have been scarcely investigated . On the other hand, it is well known that in connection with the important problems of partial differential equations of mixed type and gas dynamics of transonic currents, the construction of mathematical models describing various processes developed in media with a fractal structure leads to differential equations of fractional order.…”
Section: Introductionmentioning
confidence: 99%